Changes in supraspinal and spinal excitability of the biceps brachii following brief, non-fatiguing submaximal contractions of the elbow flexors in resistance-trained males. (21st October 2015) - Aboodarda, Saied Jalal; Copithorne, David B.; Pearcey, Gregory E.P.; Button, Duane C.; Power, Kevin E.
Highlights: Corticospinal excitability was assessed following brief non-fatiguing contractions. Supraspinal excitability is increased immediately post-exercise. Spinal excitability is decreased immediately post-exercise. Abstract: The purpose of the current study was to assess the effects of 5 brief (2 s), intermittent, submaximal elbow flexors voluntary contractions at 50% of maximal voluntary contraction (MVC) on measures of central ( i.e. supraspinal and spinal) excitability. Supraspinal and spinal excitability of the biceps brachii were assessed via transcranial magnetic stimulation (TMS) of the motor cortex and transmastoid electrical stimulation (TMES) of the corticospinal tract, respectively. TMS-induced motor-evoked potentials (MEPs), TMES-induced cervicomedullary-evoked potentials (CMEPs), Erb's point peripheral nerve stimulation and MVC were assessed prior to and following submaximal voluntary contractions at 50% of MVC. The MEP to CMEP ratio increased (584 ± 77.2%; p  = 0.011) and CMEP amplitudes decreased (62 ± 3.0%; p  = 0.02) immediately post-exercise. MVC force output did not change immediately post-exercise. The results suggest that brief, non-fatiguing intermittent submaximal voluntary contractions transiently enhance supraspinal excitability while decreasing spinal excitability. The impact of these changes on one's ability to generate or maintain force production remains unknown.